Design And Fabrication Of Shape Memory Alloy Heat Engine - Shahruddin, Nabil Syamim (Universiti Sains Malaysia, 2021)
NiTi heat engine is a simple device that converts heat energy from the heat source into mechanical energy. This conversion of energy happens due to the unique property of NiTi which shape memory effect (SME). SME is a phenomenon where NiTi can be deformed elastically into any shapes or geometry and the deformation can be completely undo by applying heat with temperature above transition temperature of NiTi. There are two types of SME which are One-way SME and Two-way SME. This project focuses on designing and fabricating NiTi heat engine that uses shape memory alloy (SMA) material as well as being able to demonstrate a properly-function SMA heat engine. The selected SMA material is a 0.5 mm ⌀ NiTi wire with a transition temperature of 80°C. This research discusses on the process of fabrication of the NiTi heat engine entirely including the methods of joining the NiTi wire to form a circular loop of NiTi and producing the pulley wheels. After the completion of fabrication process, the prototype is tested to obtain the maximum speed that be achieved. Discussion on the possible parameters such as temperature of water bath that influences the performance of the NiTi heat engine. Generally, the rotation of the NiTi heat engine is longer when being dipped in a hot water bath with higher temperature.